Microwave radiothermometry in the diagnosis and evaluation of the neoadjuvant treatment of patients with breast cancer - O. A. Sinelnikova; R. A. Kerimov; G. T. Sinyukova; S. B. Polikarpova (Опухоли женской репродуктивной системы, 2014)
Microwave mammography permits thermal changes to be estimated both within the breast and onto its surface. It is obvious that ireplace X-ray mammography or ultrasonography (USG) since it gives no information on breast structural changes, which is very nefor a physician.At the same time microwave mammography can yield additional information on the magnitude of proliferative processes and on the thermal activity of tissue. In many cases, this information may be decisive in elaborating treatment policy.Due to its simplicity , non-invasiveness, and safety , decimetric microw ave radiothermometry may be a promising method for diagno sing breast cancer and evaluating the efficiency of its treatment. When used in combination with X-ray study and USG, this technique provides incomparable assistance in defining the management of patients. The concurrent use of mammography , USG, and radiothermometric d iag- nosis of the breast assists in reducing the level of diagnostic errors to 1-3%.